A comunicação enfermeira/gestante na consulta de enfermagem em unidade de pré-natal - Oliveira, Dulce Maria Mafra (1996)
Day after day a growing necessity to study the phenomenon of communication arises, specially when such a study is related to specific groups, as one knows that it is through the deep Knowledge of the daily singularities which lie around the communicative acts that we can make of communication a practice that considers the social being. This research aimed to observe the process of communication between the nurse and the pregnant woman during the nursing consultation in a prenatal unit, by identifying the kind of communication, whether therapeutic or not, and the darriers of communication that have been felt according to the nurses opinion. The research has as informants three nurses who work in health Centers, in an interior city of the state of Bahia, Brazil, as well as seventy eight pregnant women who attended such Centers. From my observation, I have utilized a guide, where therapeutic communication strategies are found; I also have recorded each interaction between nurse and the pregnant woman, besides having done a semi-structured interview with them. The results I have drawn point out as the main cliente young and single teenagers, having low degrees of interaction; the results also point out the effective communicative acts with such women, though the nurses indicate comunicative barries owing to administrative tasks. The techniques of therapeutic communication are predominant during the process of interation between nurses and women, with special attention to the "reflexive hearing", fact that contributes to the reduction or elemination of possible mental disorders which may appear during the cycle.